LEARNING AGILITY GURU SEBAGAI PENDEKATAN PENGEMBANGAN SDM DALAM MENGHADAPI PERUBAHAN TEKNOLOGI - Riska Maya Annisa (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the role of learning agility as a human resource development approach for teachers in responding to educational technology transformation at SMP Plus Darussalam Blokagung. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observation, and documentation. The findings indicate that teachers with high learning agility demonstrate greater adaptability, pedagogical innovation, and consistency in integrating digital learning technologies. Learning agility strengthens teachers’ mental readiness, fosters instructional innovation, and enhances the effectiveness of technology-based professional development. This study contributes to the literature by extending learning agility research into the context of Islamic boarding school–based education and proposing a strategic framework for sustainable and adaptive teacher development